Improved Lane Departure Response Distortion Warning Method based on Hough Transformation and Kalman Filter - Liang, Minjian; Zhou, Zhou; Song, Qingsong (Informatica, 2017)
Lane departure warning is the key issues of automobile active safety problems. In this paper, an improved lane departure warning method is proposed based on Hough transformation and Kalman filter, noted as HK-LDWS. At first, the captured colour lane videos are decomposed into frames which are transformed and truncated into binary images subsequently. Secondly, Hough transformation is explored to detect lane lines in the truncated binary images, and Kalman filter is used to predict and track the detected lines. Finally, lane departure warnings are delivered out regarding as the predetermined safe distance based on the lateral distances. The actual road test results show that HK-LDWS can track lanes and make all departure warning correctly besides that it costs less than 35 milliseconds for per frame processing. HK-LDWS is an efficient solution for the lane departure warning problem.